PENGARUH JENIS KEMASAN TERHADAP KONDISI PENYIMPANAN GABAH KERING PANEN, RENDEMEN GILING DAN BERAS KEPALA - Tanwirul Millati; Arief RM Akbar; Susi Susi; Alia Rahmi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
Aging is a natural and spontaneous phenomenon which occurs during storage of dry grain, involving physical changes and chemical that would alter the quality of the cooking, processing, taste and nutritional value as well as affect the commercial value of rice.  Naturally aging takes a long time between 6-12 months so it is less economical. Aging may be accelerated by increasing the grain moisture content and storage temperature. Freshly harvested rough rice   contains high moisture content ranging between 21-26% and respiration  activity is still high which generate heat that can be accumulated by the packaging, so the grain temperature increases. The purpose of this study was to determine the types of packaging which can increase the temperature and RH storage, milling yield and head rice yield. Grain varieties used are Siam Pandak with five types of packaging, ie black plastic bags, sacks, cans, wood and tarpaulin, and stored for 72 hours. As a control, direct drying grain harvest is used. Observations are including temperature and RH in packaging, milling recovery and head rice yields. The results showed that all types of packaging used can increase the temperature and RH in the packaging than the temperature and RH in storage space. The most high milling recovery obtained from black plastic packaging, while the head rice yields all kinds of packaging meets the quality criteria V ISO 6128-2008 except wood packaging, although based on the percentage of head rice, tarpaulins packaging has the highest head rice.